2016
DOI: 10.1063/1.4939241
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Fe2: As simple as a Herculean labour. Neutral (Fe2), cationic (Fe2+), and anionic (Fe2−) species” [J. Chem. Phys. 142, 244304 (2015)]

Abstract: A recent paper on Fe2 [A. Kalemos, J. Chem. Phys. 142, 244304 (2015)] critiqued our previous work on the system [Hoyer et al., J. Chem. Phys. 141, 204309 (2014)]. In this comment, we explain the nature of our previously reported potential energy curve for Fe2 and we discuss our computed properties for Fe2. Additionally, we fix a labeling error that was present in our previous work, although this error is unrelated to the main point of discussion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…14, as if all the iron atoms Fe( 5 D) were in an M = 0 state. Assuming that the Fe atoms formed Fe 2 molecules would not help explain the observed lack of magnetic deflection as the ground state of Fe 2 is the highly paramagnetic 9 Σ g state [62][63][64].…”
Section: Additional Sge-type Explorations By Gerlach and Sternmentioning
confidence: 99%
“…14, as if all the iron atoms Fe( 5 D) were in an M = 0 state. Assuming that the Fe atoms formed Fe 2 molecules would not help explain the observed lack of magnetic deflection as the ground state of Fe 2 is the highly paramagnetic 9 Σ g state [62][63][64].…”
Section: Additional Sge-type Explorations By Gerlach and Sternmentioning
confidence: 99%
“…Assuming that the Fe atoms formed Fe 2 molecules would not help explain the observed lack of magnetic deflection as the ground state of Fe 2 is the highly paramagnetic 9 Σ g state. [61][62][63] Otto Stern, too, undertook additional deflection experiments with a much-improved apparatus, see Table 2. Between 1926 and 1928, Stern and his co-workers at Stern's Institut für physikalische Chemie der Hamburgischen Universität inves-tigated magnetic deflection of water molecules (and concluded that the magnetic moment involved was on the order of the nuclear magneton) and Hg atoms, [50] K, Na, and Tl atoms, [51] hydrogen atoms, [52] Bi atoms, [54] Li atoms (with an estimate of whose head and body took the shape of the edge and groove of the Stern-Gerlach magnet reads another issue of the UZM Journal showcasing an image of a split molecular beam.…”
Section: Additional Sge-type Explorations By Gerlach and Sternmentioning
confidence: 99%